EVALUATION OF VOCATIONAL LEARNING FOR STUDENTS WITH SPECIAL NEEDS - Emay Mastiani; Zulfa Rahmah Effendi; Fajar Indra Septiana (Sean Institute, 2022)
One component of learning that needs serious attention is learning evaluation. This component must be implemented to determine the effectiveness of a learning system implemented by the teacher, especially to determine the achievement of learning objectives. When viewed from the context of education for children with special needs, especially in vocational-based learning, learning evaluation has great functions and benefits because the results of these activities will obtain updated student profiles related to their actual competence in certain skills. This research was conducted to dig up an overview regarding how to plan, implement, support factors, and inhibiting factors of sewing vocational learning evaluation activities for class XI mild mental retardation students at Pancaran Iman SLB and Terate Foundation C Special School, Bandung City. Based on the research findings, it can be concluded that learning evaluation activities for mild mental retardation are carried out through the stages of planning, implementation, data checking, and reporting. The main supporting factors in learning evaluation activities are the availability of positive resources, infrastructure, and parental support. Meanwhile, the teacher's lack of knowledge of student profiles and not yet optimal management of problematic behavior in students with mild mental retardation are the main inhibiting factors found in this study.